Understanding the influence of single-walled carbon nanotube dispersion states on the microstructure and mechanical properties of wet-spun fibers. (November 2020) - Jiang, Xinrong; Gong, Wenbin; Qu, Shuxuan; Wang, Danrui; Liu, Tong; Li, Qingwen; Zhou, Gengheng; Lu, Weibang
Abstract: In this work, transmission electron microscopy (TEM) was applied to study single-walled carbon nanotube (SWCNT) dispersion states in aqueous solutions at nanoscale, and a method based on selected-area electron diffraction patterns was developed to quantitatively describe the internal SWCNT alignment across a whole fiber. Moreover, the SWCNT bundle size and pore defects were also evaluated by high-resolution TEM. It was found that the SWCNT bundle size increased from approximately 15 to 40 nm as its mass concentration increased from 0.4% to 1.0% in the spinning dope, which then influenced the SWCNT bundle size in the final fibers. Meanwhile, the degree of SWCNT alignment in the fiber increased initially and then decreased monotonically with the increased concentration. The effects of spinning needle size and length on the mechanical performance of the fibers were also discussed. The combination of the nano-structural characterizations of the spinning dopes and the final fibers sheds some light on the development of high-performance CNT fibers. Graphical abstract: Image 1